HIGH PERFORMANCE THIN LAYER CHROMATOGRAPHY (HPTLC) ANALYSIS OF EMBELIN IN DIFFERENT ORGANS / PARTS OF EMBELIA RIBES BURM F. A - V. P. SATHE; A. P. DIXIT (International Journal of Pharma and Bio Sciences, 2015)
Embelia ribes Burm F. is woody climbing shrub belonging to family Myrsinaceae, and is an important medicinal plant of Western Ghats of India. It is used as anthelmintic, carminative, stimulant, antifertility, anticancer and in Herbal cosmetics. The present study was carried out for the first time to investigate the principle bioactive constituent, embelin from different parts of the plant by HPTLC method. Mature black, red, green colour fruits, leaves and fruit cover showed characteristic peaks of embelin. However, a lot of variation in the % of embelin content was observed among the samples of different parts. High percentage of embelin content was observed in mature red colour fruits sample. The HPTLC method has given the reliable quantification of embelin from different organs of Embelia ribes. This method can be used for analytical work and for selection of plant part for commercial exploitation. It will help to prepared the monograph of Embelia ribes.